Print media coverage of breastfeeding in Great Britain: Positive or negative?. (24th November 2022) - Merritt, Rowena; Eida, Tamsyn; Safon, Cara; Kendall, Sally
Abstract: Media can be a powerful communication tool to promote breastfeeding, influence mothers' breastfeeding behaviour, create positive social norms and generate support among stakeholders and policymakers for breastfeeding. However, negative stories could deter women from starting or continuing to breastfeed. This study aimed to describe the breadth and focus of the media coverage of breastfeeding and the message frames that are found in three of the most widely read national newspapers and three popular women's magazines in Great Britain over a 12‐month period, as part of the Becoming Breastfeeding Friendly in Great Britain (BBF‐GB) study. For this retrospective media analysis, 77 articles were identified and 42 were included in the study for coding and analysis. We conducted two content analyses to examine the articles' (1) message framing and (2) alignment with the eight components of an 'enabling breastfeeding environment' using the BBF Gear framework. Articles featuring breastfeeding appear in British newspapers and women's magazines all year round. Twenty‐four per cent had a neutral tone, while 59% predominantly focused on the positive aspects or positive social support for breastfeeding, and 17% were predominantly focused on the negative aspects or negative social attitudes towards breastfeeding. The articles mainly focused on personal stories reflecting societal barriers and positive shifts (68%), with 12% presenting an analysis of breastfeeding evidence or barriers. There were fewer references to the legislation (5%) and availability of funding (2%) and support (9%). There was no coverage of national coordination and strategy, evaluation systems, or the political will to raise breastfeeding rates. Abstract : Article focus, by percentage Key messages: During the one‐year study period, articles featuring breastfeeding appeared in the included British newspapers and women's magazines all year round rather than being focused on specific events, such as World Breastfeeding Week. Articles mainly focused on personal stories and were initiated by social media posts or discussions on television by mothers, often celebrity mothers. While articles discussed the difficulties mothers face during breastfeeding, they also detailed positive support for breastfeeding, presenting a more balanced view. The articles did not fully reflect BBF's Gear Model components for an enabling breastfeeding environment. Most were categorised as promotion articles with fewer advocacy pieces. There was little coverage of legislation, services and funding while political support, breastfeeding data and strategic oversight were not covered.